2023
DOI: 10.3390/jcm12072705
|View full text |Cite
|
Sign up to set email alerts
|

Association between Preoperative Hand Grip Strength and Postoperative Delirium after Cardiovascular Surgery: A Retrospective Study

Abstract: The association of frailty with postoperative delirium has not been fully investigated in patients undergoing cardiovascular surgery. Therefore, this study aimed to investigate whether preoperative hand grip strength is associated with postoperative delirium. This retrospective study included patients aged >65 years who had undergone elective cardiovascular surgery using cardiopulmonary bypass at a Japanese university hospital between April 2020 and February 2022. We defined low hand grip strength as hand g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“… 13 , 14 Moreover, some published studies have shown that low preoperative hand grip strength was an independent predictor of delirium after surgery. 15 , 16 However, there has been a paucity of research on the effect of grip strength before surgery on the occurrence of SSD in older patients undergoing joint replacement so far. Therefore, this study aimed to investigate the association between grip strength and SSD in older patients after joint replacement surgery.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Moreover, some published studies have shown that low preoperative hand grip strength was an independent predictor of delirium after surgery. 15 , 16 However, there has been a paucity of research on the effect of grip strength before surgery on the occurrence of SSD in older patients undergoing joint replacement so far. Therefore, this study aimed to investigate the association between grip strength and SSD in older patients after joint replacement surgery.…”
Section: Introductionmentioning
confidence: 99%